Studies on Mechanical Properties of Jute Fiber Composite Panels. (2019) - Valarmathi, T.N.; Arputhabalan, J. Jeswinw; Ravichandran, S.; Robin, S.; Revanth, V.; Sekar, S.
Abstract: Composite materials are widely used in many fields because of their superior qualities. Nowadays natural fibers are finding becoming good choice as they are cheap, safe to manufacture, recyclable, biodegradable and eco-friendly. In this study, Jute fiber and epoxy composite and Jute fiber and epoxy with Al metal powder composite panels of 5mm thickness is fabricated using hand layup method to investigate their tensile strength and hardness.